ショウワキチ フキン ノ リクジョウ ショクブツ グンラク ノ ブンプ ト スイブン オヨビ ヨウブン トノ カンケイ - 山中, 三男; ヤマナカ, ミツオ; 佐藤, 和夫; サトウ, カズオ; Yamanaka, Mitsuo; Sato, Kazuo (国立極地研究所, 1977)
P(論文) 昭和基地付近の露岩地域における蘚類・藻類を主とする陸上植物群落の分布と,水環境および養分環境との関連を追跡するため,野外調査と室内での分析実験を行った.野外調査はこれまであまり調査されていなかった大陸の小露岩地帯に重点をおいた.その結果,これら小露岩地帯の植物群落の分布と水供給,さらにそれと密接な関係のある地形との間に,島の露岩地帯の場合とは異なった関連性が見出された.土壌分析の結果からは,全窒素,全炭素および有効態リン酸と植物群落の分布および海鳥類の活動との間に,ある程度の対応関係が推察された.また,ラン藻類の一種が,蘚類に対して養分供給の面でなんらかの作用をしているのではないかと思われる現象がみられた.置換性塩基と植物群落と分布との間には,今回の研究ではとくに対応関係は見出されなかった. The ecological studies were made on the terrestrial plant communities (mainly mosses and algae), with special reference to water supply and soil properties. Moss communities were distributed mainly on the northeastern and northwestern slopes of the bare-rock zones, such as Akarui Point, Tama Point, Tensoku Rock, Tottuki Point and Mukai Rocks, where water is supplied directly from the ends of the continental ice sheet in the summer. To elucidate the relation between distribution pattern of plant communities and nutrients, the soil samples for chemical analyses were taken at 37 points in various areas, and pH, total N, total C, available P_2O_5 and exchangeable Ca, Mg, K and Na were measured in the laboratory. The correlations were observed, to a certain extent, among moss community and total N and C. It can be said that available P_2O_5 plays an important role in distribution and growth of a species of green alga (Prasiola crispa subsp. antarctica). On the other hand, many points remain uncertain regarding the relation between the distribution of plants and the inorganic nutrients such as Ca, Mg, K and Na. departmental bulletin paper